DETEKSI FINANCIAL DISTRESS BAGI PERUSAHAAN BANK UMUM YANG TERDAFTAR DI BEI (BURSA EFEK INDONESIA) SAAT PANDEMI COVID 19 - Febrianto, Gustaf Naufan (JEM17: Jurnal Ekonomi Manajemen, 2021)
The purpose of this study is to examine the effect of macro economy, risk profile to firm performance and Financial Distress in Conventional Bank foreign exchange go public listed in Indonesia stock exchange at pandemic covid 19. The sample used in this research is 44 companies with 1 years observation from 2019-2020 (Covid-19). Analysis of research data using Desriptive Qualitative. The results showed: Macro economy has a significant effect on firm performance and also significant effect on Financial Distress. Risk Profile significant effect on firm performance And have significant effect onFinancial Distress, firm performance significantly influence the Financial Distress